Development of a Real-Time Repeated-Measures Assessment Protocol to Capture Change over the Course of a Drinking Episode. - Luczak, Susan E.; Rosen, I. Gary; Wall, Tamara L. (Alcohol & Alcoholism, 2015)
Aims: We report on the development of a real-time assessment protocol that allows researchers to assess change in BrAC, alcohol responses, behaviors, and contexts over the course of a drinking event. Method: We designed a web application that uses timed text messages (adjusted based on consumption pattern) containing links to our website to obtain real-time participant reports; camera and location features were also incorporated into the protocol. We used a transdermal alcohol sensor device along with software we designed to convert transdermal data into estimated BrAC. Thirty-two college students completed a laboratory session followed by a 2-week field trial. Results: Results for the web application indicated we were able to create an effective tool for obtaining repeated measures real-time drinking data. Participants were willing to monitor their drinking behavior with the web application, and this did not appear to strongly affect drinking behavior during, or 6 weeks following, the field trial. Results for the transdermal device highlighted the willingness of participants to wear the device despite some discomfort, but technical difficulties resulted in limited valid data. Conclusion: The development of this protocol makes it possible to capture detailed assessment of change over the course of naturalistic drinking episodes.